Magnetic Doppler Imaging of He-strong star HD 184927. Issue Volume 9:Issue S302(2013) (7th August 2014) - Yakunin, I.; Wade, G.; Bohlender, D.; Kochukhov, O.; Tsymbal, V.; ,
Abstract: We have employed an extensive new timeseries of Stokes I and V spectra obtained with the ESPaDOnS spectropolarimeter at the 3.6-m Canada-France-Hawaii Telescope to investigate the physical parameters, chemical abundance distributions and magnetic field topology of the slowly-rotating He-strong star HD 184927. We infer a rotation period of 9 d .53071 ± 0.00120 from Hα, Hβ, LSD magnetic measurements and EWs of helium lines. We used an extensive NLTE TLUSTY grid along with the SYNSPEC code to model the observed spectra and find a new value of luminosity. In this poster we present the derived physical parameters of the star and the results of Magnetic Doppler Imaging analysis of the Stokes I and V profiles. Wide wings of helium lines can be described only under the assumption of the presence of a large, very helium-rich spot.